Engineered Corynebacterium glutamicum as the Platform for the Production of Aromatic Aldehydes - Kim, Hyun-Song; Choi, Jung-A; Kim, Bu-Yeon; Ferrer, Lenny; Choi, Jung-Min; Wendisch, Volker F.; Lee, Jin-Ho (Frontiers in Bioengineering and Biotechnology, 2022)
Aromatic aldehydes, including 4-hydroxybenzaldehyde (4-HB aldehyde), protocatechuic (PC) aldehyde, and vanillin, are important flavors, fragrances, and pharmaceutical precursors and have several biological and therapeutic effects. Production of aromatic aldehydes in the microbial hosts poses a challenge due to its rapid and endogenous reduction to alcohols. To address this hurdle, prospecting of the genome of Corynebacterium glutamicum yielded twenty seven candidate proteins that were used in a comprehensive screening with a 4-hydroxybenzyl (4-HB) alcohol-producing strain. We identified that NCgl0324 has aromatic aldehyde reductase activity and contributed to 4-HB aldehyde reduction in vivo since the NCgl0324 deletion strain HB-Δ0324 produced 1.36 g/L of 4-HB aldehyde, i.e., about 188% more than its parental strain. To demonstrate that NCgl0324 knockout can also improve production of PC aldehyde and vanillin, first, a basal MA303 strain which produces protocatechuate was engineered from 4-hydroxybenzoate-synthesizing C. glutamicum APS963, followed by deletion of NCgl0324 to generate PV-Δ0324. PC aldehyde/alcohol or vanillin/vanillyl alcohol biosynthetic pathway, respectively, was able to be expanded from protocatechuate upon introduction of carboxylic acid reductase (CAR) or CAR and catechol O-methyltransferase encoded by a mutated comtm gene. In shake flask culture, the resulting NCgl0324 deletion strains PV-IΔ0324 and PV-IYΔ0324 were shown to produce 1.18 g/L PC aldehyde and 0.31 g/L vanillin, respectively. Thus, modulation of the identified NCgl0324 gene was shown to have the potential to boost production of valuable aromatic aldehydes.